PERUMUSAN STRATEGI DESA WISATA GROGOL DI MASA PANDEMI (Studi Kasus di Desa Wisata Grogol Kecamatan Seyegan Kabupaten Sleman) - Dwi Cahyani (universitas teuku umar, 2021)
The tourist village is a form of integration between attractions, accommodations, and supporting facilities that are presented in a structure of community life that is integrated with applicable procedures and traditions. Strategy is a tool to achieve long-term goals. External changes due to the COVID-19 pandemic have forced tourist villages to formulate new strategies. The purpose of this study is to identify opportunities and threats to the external environment as well as the strengths and weaknesses of the internal environment of the Grogol Tourism Village, to identify alternative strategies that can be implemented according to the SWOT and IE matrix, to analyze the current decisions taken by the Grogol Tourism Village based on the QSPM matrix. The type of research used is a case study. The type of research data is primary data. The methods of collecting data are observation and interviews. The data analysis technique is the IFE, EFE, SWOT, IE and QSPM matrices. The total EFE is 3.12 and the total IFE is 3.41. The results of the QSPM have 4 alternative strategies, namely providing more choices of tour packages, developing creative industries with the community, cooperating with the millennial generation, and increasing tourist attraction as a competitive advantage.